AP-7 into the nucleus accumbens disrupts acquisition but does not affect consolidation in a passive avoidance task - Martínez, Gabriel (2002)
The effect of the blockade of N-methyl-D-aspartic acid (NMDA)-type glutamatergic receptors in the nucleus accumbens septi (Acc) during different phases of a passive avoidance task (step-through paradigm, two chambers) of learning was studied in male rats which had been bilaterally cannulated into the Acc. Animals were trained with a punishment procedure (3 s shock of 1 mA) to avoid one of the chambers. The rats received either saline or (±)2-amino-7-phosphonoheptanoic acid (AP-7) solution (1 μg/1 μl) 10 min before training (pretraining schedule) or immediately after the shock (posttraining schedule). In the test phase, the animals were placed back into the white chamber after 1 and 8 days later. In this moment, rats stayed there for 1 min, after which the time elapsed between the removal of the door to the introduction into the dark chamber of the head (Latency 1) and body (Latency 2) and fecal boli expelled were recorded. In the pretraining injection schedule, the drug treatment significantly reduced Latency 2 (P<.05) and fecal boli (P<0.01) on Day 1, and all parameters on Day 8 (P<.05). The posttraining injection schedule did not modify behavior. We conclude that a preshock NMDA-glutamatergic blockade of the Acc leads to cognitive disturbances during acquisition and a decrease in anxiety levels, but that the consolidation of a learned task is not affected by postshock administration.